Elongating, entwining, and dragging: mechanism for adaptive locomotion of tubificine worm blobs in a confined environment - Mikami, Taishi; Wakita, Daiki; Kobayashi, Ryo; Ishiguro, Akio; Kano, Takeshi (Frontiers in Neurorobotics, 2023)
Worms often aggregate through physical connections and exhibit remarkable functions such as efficient migration, survival under environmental changes, and defence against predators. In particular, entangled blobs demonstrate versatile behaviours for their survival; they form spherical blobs and migrate collectively by flexibly changing their shape in response to the environment. In contrast to previous studies on the collective behaviour of worm blobs that focused on locomotion in a flat environment, we investigated the mechanisms underlying their adaptive motion in confined environments, focusing on tubificine worm collectives. We first performed several behavioural experiments to observe the aggregation process, collective response to aversive stimuli, the motion of a few worms, and blob motion in confined spaces with and without pegs. We found the blob deformed and passed through a narrow passage using environmental heterogeneities. Based on these behavioural findings, we constructed a simple two-dimensional agent-based model wherein the flexible body of a worm was described as a cross-shaped agent that could deform, rotate, and translate. The simulations demonstrated that the behavioural findings were well reproduced. Our findings aid in understanding how physical interactions contribute to generating adaptive collective behaviours in real-world environments as well as in designing novel swarm robotic systems consisting of soft agents.